From Hope to Heartache: A Case Report of Treatment Failure and its Impact on a 1-year-old with Bilateral Radial Aplasia in a Resource-Limited Setting - Oluwatosin Gabriel Afolabi; Ademola Samuel Adeyemi; Imiekame Mimi Aitalokhai (Journal of Orthopaedic Case Reports)
Introduction: Radial aplasia is a rare congenital anomaly of the upper limbs, more common in females, affecting between one in 30,000 and one in 100,000 live births, and primarily impacting structures on the radial side of the forearm. While there have been numerous articles on bilateral radial aplasia and its management, this case is particularly significant as it represents the index case for our hospital. It is the first report to highlight how limited resources can lead to unfavorable outcomes in the management of this condition. In addition, it aims to stimulate the interest of the global orthopedics community to develop interventions or modify current treatment options that can be successfully implemented in low-resource settings to improve outcomes, especially the functionality of the limbs. By documenting this case, we aim to shed light on the challenges faced in resource-limited settings and advocate for increased investment in training pediatric orthopedic specialist to enhance the quality of life for affected children. Case Report: A 1-year-old boy of African descent presented with bilateral radial club hand. The patient exhibited characteristics of classical radial club hand, with complete absence of the radius and thumbs bilaterally, resulting in the nonexistence of the radio-carpal and radio-ulna joints. The forearm and ulna were shorter, with the ulna’s diaphysis curved toward the radius. No hematological abnormalities were noted, and the case was non-syndromic with no identifiable risk factors. The patient underwent serial manipulation and casting for 17 months to achieve sufficient soft tissue stretching and passive correction of the deformity before the centralization procedure. Conclusion: This case underscores the urgent need for improved access to specialized pediatric orthopedic care, advanced intraoperative imaging tools, and comprehensive, continuous parent education on realistic treatment expectations for patients with bilateral radial club hand. Addressing these limitations can enhance long-term outcomes and quality of life for children with this condition. This case report is of particular interest to both current and intending pediatric orthopedic specialists and highlights the broader clinical impact of resource limitations on treatment outcomes. In addition, it significantly advances our knowledge of the challenges faced in managing severe congenital anomalies in resource-limited settings.